Studi Komparasi Penggunaan Strategi NHT dengan STAD terhadap Hasil Belajar Matematika Siswa Kelas IV SDN Mojolegi Tahun 2015/2016 - Prima Leksikowati, Ayunda (2016)
This study uses a quantitative study with experimental method. This research aimed to know. (1) The difference between the results of mathematics learning strategy use NHT (Numbered Heads Together) with STAD (Student Teams Achievement Division) in the fourth grade students of SDN Mojolegi Year 2015/2016. (2) The effect of a larger strategy of NHT (Numbered Heads Together) with STAD (Student Teams Achievement Division) against the results of studying Maths grade IV SDN Mojolegi. This study uses a quantitative study with experimental method. Subject of research is the fourth grade students of SDN Mojolegi year 2015/2016. The data collection technique using the techniques of tests and documentation. Techniques of analysis using t tests were preceded by the prerequisite test analysis is the homogeneity test and test for normality. Based on data analysis with a significance level of 5% was obtained thitung>ttabel, namely 2.455 > 2.001 and the average results of studying Maths class IV A strategy NHT (Numbered Heads Together) and class IV B with STAD (Student Teams Achievement Division) is 75,17 > 69.67. The conclusion of this study were (1) no differences in outcomes between the mathematics learning strategy use NHT (Numbered Heads Together) with STAD (Student Teams Achievement Division) in the fourth grade students of SDN Mojolegi Year 2015/2016. (2) Strategy NHT (Numbered Heads Together) greater influence tehadap mathematics learning outcomes compared STAD (Student Teams Achievement Division) in the fourth grade students of SDN Mojolegi.